Characterizing Factors Associated With Differences in FGF19 Blood Levels and Synthesis in Patients With Primary Bile Acid Diarrhea. (March 2016) - Johnston, Ian M; Nolan, Jonathan D; Pattni, Sanjeev S; Appleby, Richard N; Zhang, Justine H; Kennie, Sarah L; Madhan, Gaganjit K; Jameie‐Oskooei, Sina; Pathmasrirengam, Shivani; Lin, Jeremy; Hong, Albert; Dixon, Peter H; et al.
Abstract : OBJECTIVES: Chronic diarrhea caused by primary bile acid diarrhea (PBAD) is a common condition. We have previously shown PBAD is associated with low fasting serum levels of the ileal hormone, fibroblast growth factor 19 (FGF19). FGF19 is a negative regulator of hepatic bile acid synthesis and is stimulated by farnesoid X receptor agonists, which produce symptomatic improvement in PBAD. We aimed to assess possible causes for low serum FGF19 in patients with PBAD. METHODS: Patients with PBAD, defined by reduced 75 Se‐labelled homocholic acid taurine (SeHCAT) retention, and idiopathic diarrhea controls had measurements of fasting lipids and fasting/post‐prandial FGF19 serum profiles. Specific functional variants in candidate genes were investigated in exploratory studies. In further groups, basal and bile acid‐stimulated transcript expression was determined in ileal biopsies and explant cultures by quantitative PCR. RESULTS: FGF19 profiles in PBAD patients included low fasting and meal‐stimulated responses, which were both strongly correlated with SeHCAT. A subgroup of 30% of PBAD patients had fasting hypertriglyceridemia and higher FGF19. No clear significant differences were found for any genetic variant but there were borderline associations with FGFR4 and KLB . SeHCAT retention significantly correlated with the basal ileal transcript expression of FGF19 ( r s =0.59, P =0.03) and apical sodium‐dependent bile acid transporter (ASBT) ( r s =0.49, P =0.04), and also with the degree of stimulation by chenodeoxycholic acid at 6 h for transcripts of FGF19 (median 184‐fold, r s =0.50, P =0.02) and ileal bile acid binding protein (IBABP) (median 2.2‐fold, r s =0.47, P =0.04). Median stimulation of FGF19 was lower in patients with SeHCAT retention <10% ( P =0.01). CONCLUSIONS: These studies demonstrate a complex, multifactorial etiology of PBAD, including impairments in ileal FGF19 expression and responsiveness.